1998
DOI: 10.1097/00007632-199809010-00018
|View full text |Cite
|
Sign up to set email alerts
|

Sequential or Simultaneous, Same-Day Anterior Decompression and Posterior Stabilization in the Management of Vertebral Osteomyelitis of the Lumbar Spine

Abstract: Patients with lumbar osteomyelitis necessitating surgery can undergo combined, same-day surgery either in a sequential or simultaneous manner. This is a safe and efficient way to control the infection and stabilize the affected segments, allowing for early mobilization of these sick elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 11 publications
4
76
0
1
Order By: Relevance
“…Moon et al [22] suggested that posterior surgery was useful for early control of the disease, early fusion and prevention of kyphosis progression. Safran et al [28] showed that anterior decompression and posterior stabilization at the same day was an effective and safe method of controlling the disease and stabilization of the affected segments. Klockner et al [16] suggested that posterior instrumentation should be combined with anterior debridement and fusion in deformities affecting many levels and/or in excessive kyphotic deformities.…”
Section: Discussionmentioning
confidence: 99%
“…Moon et al [22] suggested that posterior surgery was useful for early control of the disease, early fusion and prevention of kyphosis progression. Safran et al [28] showed that anterior decompression and posterior stabilization at the same day was an effective and safe method of controlling the disease and stabilization of the affected segments. Klockner et al [16] suggested that posterior instrumentation should be combined with anterior debridement and fusion in deformities affecting many levels and/or in excessive kyphotic deformities.…”
Section: Discussionmentioning
confidence: 99%
“…These patients usually need to be maintained in bed after surgery, and the duration of bedrest will depend upon the degree of stability achieved at operation. Therefore, addition of posterior instrumentation in a noncontaminated field seems to be a more logical choice of treatment modalities to avoid graft displacement and facilitate early rehabilitation [3,5,10,11,15,19,21,27,31,36,41,46]. In some cases treated with posterior instrumentation, a cyclindrical titanium cage filled with bone graft has been also used as an alternative to structural bone grafting [17,25,28,29,32,36,48].…”
Section: Discussionmentioning
confidence: 99%
“…However, inspired by the methods of surgical management of severe scoliosis in which a combined single-stage operation was routinely used, some surgeons tried to use the single-staged surgery for the treatment of pyogenic vertebral osteomyelitis. The results indicated that single-staged operation also has many advantages such as lower complication rate, shorter hospital stay, and earlier mobilization as compared to its counterpart [13,23,36,70]. In 1988, Redfern and colleagues [67] presented a series of six patients with pyogenic osteomyelitis treated with single-staged debridement and posterior instrumentation.…”
Section: Single-stage or Two-stage Operationmentioning
confidence: 99%